Mixed-methods assessment of electronic medical record implementation and its effects on medical record work units in hospital - Adhani Windari; Retnowati Retnowati; Subinarto Subinarto; Puput Sugiarto (Jurnal Konseling dan Pendidikan, 2025)
The Regulation of the Minister of Health Number 24 of 2022 mandates that all healthcare facilities in Indonesia implement Electronic Medical Records (EMR) to improve the quality and efficiency of health services. In response to this policy, this study utilized a cross-sectional mixed-methods approach to evaluate the implementation of EMR and its impact on medical record work units in a regional hospital. A total of 26 EMR users, consisting of medical record officers and relevant health workers, were selected through total sampling to provide both quantitative and qualitative data. The evaluation framework integrates the End User Computing Satisfaction (EUCS) and Technology Acceptance Model (TAM) to assess system quality, information quality, user satisfaction, and intention to continue using EMR. Quantitative findings demonstrate that information quality and system quality have strong and statistically significant relationships with intention to use EMR (p = 0.001), explaining 66.3% and 52.8% of the variance, respectively. Meanwhile, thematic analysis of qualitative data reveals that EMR enhances workflow efficiency, accelerates information retrieval, and strengthens service coordination across hospital units. However, challenges such as occasional system downtime, limited digital literacy among some users, and incomplete menu features still hinder optimal utilization. The integrated interpretation indicates that sustained user acceptance relies on the alignment between perceived usefulness and reliable system performance. This study underscores the need for continuous system refinement, structured and ongoing training, and adequate resource support to ensure EMR implementation contributes effectively to hospital service quality and digital health transformation in Indonesia.